If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + 2) + -16 = 0 Reorder the terms: (2 + 6x) + -16 = 0 Remove parenthesis around (2 + 6x) 2 + 6x + -16 = 0 Reorder the terms: 2 + -16 + 6x = 0 Combine like terms: 2 + -16 = -14 -14 + 6x = 0 Solving -14 + 6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 6x = 0 + 14 Combine like terms: -14 + 14 = 0 0 + 6x = 0 + 14 6x = 0 + 14 Combine like terms: 0 + 14 = 14 6x = 14 Divide each side by '6'. x = 2.333333333 Simplifying x = 2.333333333
| 8c-4/6c-3 | | 9x^2-24x-65=0 | | -7/3×n=-42 | | logx=2.45 | | -42-32r= | | 23+21z= | | B*8=96 | | -11v= | | 48=8-10n | | s^2+15s+20=0 | | 10x+5x-3x=120 | | 1+20xX=Y | | 4x-10x=14 | | .375x-13=-25 | | 0.66666666666x-6=9 | | 6-7=10y+4-9y | | (x*.055)+x=650 | | 8(c+10)20= | | -3(6p+2)-5p=63 | | 67=4(5+4b)-1 | | x^(1/3)/x^(1/4)*x^(-3/4) | | -13=4n-3+n | | 72=3(-5n-1) | | 0.66666666666x-2=7 | | 2cos(2x-y)dx-cos(2x-y)dy=0 | | 9.8*7.9= | | 5x*(x+50)=29950 | | 21+7=31.64 | | 3p-7=-(p-4) | | 100=-4(6x-1) | | 5x-12=8-2x | | x^2-8+1=10 |